Different MAPT haplotypes influence expression of total MAPT in postmortem brain tissue - Tauber, Christina V.; Schwarz, Sigrid C.; Rösler, Thomas W.; Arzberger, Thomas; Gentleman, Steve; Windl, Otto; Krumbiegel, Mandy; Reis, André; Ruf, Viktoria C.; Herms, Jochen; Höglinger, Günter U. (Acta Neuropathologica Communications, 2023)
The MAPT gene, encoding the microtubule-associated protein tau on chromosome 17q21.31, is result of an inversion polymorphism, leading to two allelic variants (H1 and H2). Homozygosity for the more common haplotype H1 is associated with an increased risk for several tauopathies, but also for the synucleinopathy Parkinson’s disease (PD). In the present study, we aimed to clarify whether the MAPT haplotype influences expression of MAPT and SNCA, encoding the protein α-synuclein (α-syn), on mRNA and protein levels in postmortem brains of PD patients and controls. We also investigated mRNA expression of several other MAPT haplotype-encoded genes. Postmortem tissues from cortex of fusiform gyrus (ctx-fg) and of the cerebellar hemisphere (ctx-cbl) of neuropathologically confirmed PD patients (n = 95) and age- and sex-matched controls (n = 81) were MAPT haplotype genotyped to identify cases homozygous for either H1 or H2. Relative expression of genes was quantified using real-time qPCR; soluble and insoluble protein levels of tau and α-syn were determined by Western blotting. Homozygosity for H1 versus H2 was associated with increased total MAPT mRNA expression in ctx-fg regardless of disease state. Inversely, H2 homozygosity was associated with markedly increased expression of the corresponding antisense MAPT-AS1 in ctx-cbl. PD patients had higher levels of insoluble 0N3R and 1N4R tau isoforms regardless of the MAPT genotype. The increased presence of insoluble α-syn in PD patients in ctx-fg validated the selected postmortem brain tissue. Our findings in this small, but well controlled cohort of PD and controls support a putative biological relevance of tau in PD. However, we did not identify any link between the disease-predisposing H1/H1 associated overexpression of MAPT with PD status. Further studies are required to gain a deeper understanding of the potential regulatory role of MAPT-AS1 and its association to the disease-protective H2/H2 condition in the context of PD.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Gene expression; H1 and H2 haplotype; MAPT; Parkinson’s disease; Postmortem human brain; Protein level; Synucleins; Tau protein